Bubastoides kadleci sp. nov. from Yemen (Coleoptera: Buprestidae: Bubastini) - Bílý, Svatopluk (Zootaxa, 2008)
Kerremans (1909) described the strange buprestid genus Bubastoides Kerremans, 1909 (type species: B. argodi Kerremans, 1909, by monotypy) from Somalia, which was later (Obenberger, 1920a) attributed to the Australian tribe Bubastini Obenberger, 1920 together with the genera Bubastes Laporte & Gory, 1836, Eububastes Obenberger, 1930, Euryspilus Lacordaire, 1857, Neobubastes Blackburn, 1892, Neurybia Théry, 1910, Notobubastes Carter, 1924, Paratassa Marseul, 1882, Schoutedenia Obenberger, 1924 and Strandiola Obenberger, 1920. Some of these genera were later synonymised with other taxa or transferred to different tribes so that the tribe Bubastini comprises at present (Bellamy, 2003) only the genera Bubastes, Bubastoides, Euryspilus, Microcastalia Heller, 1891, Notobubastes and Strandiola.